Hirschsprung disease in an adult: Too late to diagnose? (Indian Journal of Case Reports, 2020)
Adult Hirschsprung disease is a rare disorder of the hindgut that is frequently misdiagnosed as refractory constipation. About 94% of Hirschsprung disease cases are diagnosed before the patient reaches 5 years of age, however, on a rare occasion, mild cases may go undiagnosed until he or she reaches adulthood. We are presenting the case of an 18-year-old male who came with acute intestinal obstruction with a history of refractory constipation since childhood. Exploratory laparotomy with sigmoid diversion colostomy was done along with full-thickness rectal biopsy. Rectal biopsy showed the absence of ganglion cells. The patient got symptomatically relieved. Therefore, a high suspicion of Hirschsprung disease should be kept in adults having a history of repeated episodes of obstruction since childhood.